1983
DOI: 10.1002/bip.360220135
|View full text |Cite
|
Sign up to set email alerts
|

Sequential hydration of a dry globular protein

Abstract: SynopsisUsing direct difference ir and laser Raman spectroscopy, the sequential hydration of hen egg-white lysozyme was monitored. The ir data allowed us to identify some specific molecular hydration events that occur as water is added, whereas the Raman is interpreted in terms of conformational changes. The largest of these solvent-induced changes occurs below the hydration level a t which activity commences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Silver and Karel (26) studied the behavior of invertase in model systems at low moisture contents, and found that the kinetics of sucrose hydrolysis in the low moisture region were best represented by a model in which water activity affects enzyme conformation, or diffusion resistance in a resistance shell in the immediate vicinity of the enzyme molecule. This entirely phenomenologically based interpretation of the kinetics receives strong support from a recent crystallographic study by Poole and Finney (22). These authors used direct difference IR and laser Raman spectroscopy to monitor sequential hydration of lysozyme.…”
Section: Enzyme Activity and Conformation Of Polymer Chainsmentioning
confidence: 91%
“…Silver and Karel (26) studied the behavior of invertase in model systems at low moisture contents, and found that the kinetics of sucrose hydrolysis in the low moisture region were best represented by a model in which water activity affects enzyme conformation, or diffusion resistance in a resistance shell in the immediate vicinity of the enzyme molecule. This entirely phenomenologically based interpretation of the kinetics receives strong support from a recent crystallographic study by Poole and Finney (22). These authors used direct difference IR and laser Raman spectroscopy to monitor sequential hydration of lysozyme.…”
Section: Enzyme Activity and Conformation Of Polymer Chainsmentioning
confidence: 91%
“…Especially in the last several years, a growing number of food scientists from both academia and industry have increasingly recognized the practical significance of the glass transition as a Slade and Levine 1985, 1988a,b, 1991aGould and Christian 1988;Sapru and Labuza 1992a,b;Bolton et a/ 1993Bolton et a/ 1989Slade et al 1989;Myers-Betts and Baianu 1990;Oksanen and Zografi 1990;Ablett and Lillford 1991 ;Franks 1991a,b;Slade and Levine 1991a Cole et al 1983Levine and Slade 1986, 1988c,d, 1989c,d, 1990Blanshard and Van den Berg 1981Slade 1988a, 1989b;Lillford 1988;Cairault et al Franks 1987;Hirsh 1987;Franks 1989Franks , 1990Franks and Hatley 1990;Le Meste and Simatos 1990;Noel et 01 1990;Pika1 1990a,b;Belton 1991;Blond and Colas 1991;Chang and Baust 1991as;Franks and Van den Berg 1991 ; Franks et nl 1991 ; Lim and Reid 1991;Roos and Karel 1991f,g;Best 1992;Blond 1992;Caldwcll et al 1992;Chang and Randall 1992;Goff 1992;Goff et al 1992;Karel 1992;Nesvadba 1992a; Van den Berg 1992; Van den Berg et al 1992…”
Section: T and Methods Of Its Measurement In Foodsmentioning
confidence: 97%
“…As the name implies, water dynamics focuses on (i) the mobility (Chinachoti et al 1991b; Larsson 1991 ; Tanner et a1 1991 ; Goff 1992) and eventual 'availability' (Ablett and Lillford 1991 ; Franks 199 1 b) of the plasticizing diluent (be it water alone or an aqueous solution) ; and (ii) an interpretive approach to understanding how to control the mobility of the diluent in glass-forming food systems that would be inherently mobile, unstable and reactive at temperatures and moisture contents corresponding to the rubbery liquid state at T > (Slade and Levine 1991a). This concept (along with that of glass dynamics) has provided an innovative perspective on water relationships in foods Ablett and Lillford 1991 ;Franks 1991b;Goff 1992;Karel 1992;Nelson and Labuza 1992a;Roos 1992b; Table 3(B)), including, for example, moisture management and structural stabilization of IMF systems , 1988a and 'cryostabilization' of frozen, freezer-stored and freezedried aqueous glass-forming food materials and products (Cole el a1 1983Levine and Slade 1986, 1988a4, 1989a4, 1990. This perspective, the focal point of which is the critical importance of the glassy state phenomenon in foods, has received considerable recent support from many workers in the field (Table 10( A)).…”
Section: 'Water Dynamics' and 'Glass Dynamics'mentioning
confidence: 97%
“…This conclusion was supported by some hydrogen isotope-exchange studies (6,7) but contradicted by others (8). Raman (9)(10)(11) and solid-state NMR (12) studies have suggested significant (reversible) structural changes occurring in lysozyme upon lyophilization. Likewise, recent hydrogen isotope-exchange/high-resolution NMR (13) and FTIR (14,15) investigations of various proteins strongly point to lyophilization-induced reversible denaturation.…”
mentioning
confidence: 95%